2015
DOI: 10.3233/ch-141865
|View full text |Cite
|
Sign up to set email alerts
|

Cell-derived microparticles after exercise in individuals with G6PD Viangchan

Abstract: Glucose-6-phospate dehydrogenase (G6PD) deficient cells are sensitive to oxidative damage leading to the formation of microparticles (MPs). Therefore, we examined the concentration of MPs and changes in the antioxidant balance after an acute strenuous exercise (SEx) and moderate-intensity exercise (MEx). Eighteen healthy females (18-24 years) with G6PD normal and eighteen age-matched females with G6PD Viangchan (871G>A) were tested by running on a treadmill at their maximal oxygen uptake for SEx and at 75% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Differently from the results of other studies, in which no difference or an increase in postexercise platelet-derived EVs (particularly, CD41a+ or CD42b+ EVs) was found [19,35,36], a decrease in CD61+ EVs occurred in our study population after acute exercise. Interestingly, this effect was more evident at 24h after the end of the test.…”
Section: Discussioncontrasting
confidence: 99%
“…Differently from the results of other studies, in which no difference or an increase in postexercise platelet-derived EVs (particularly, CD41a+ or CD42b+ EVs) was found [19,35,36], a decrease in CD61+ EVs occurred in our study population after acute exercise. Interestingly, this effect was more evident at 24h after the end of the test.…”
Section: Discussioncontrasting
confidence: 99%
“…Other findings on the clinical manifestations of G6PDd were described in four articles. 69–72 A study in Thailand found that among females with the G6PD Viangchan mutation, strenuous exercise induced a significantly higher increase in total microparticle level (an indicator of oxidative damage) compared with age-matched G6PD normal females. 69 In a study from Thailand, the authors suggested that excessive fluoride in drinking water might worsen the effect of iron deficiency anaemia, thalassemia and G6PDd.…”
Section: Resultsmentioning
confidence: 99%
“… 69–72 A study in Thailand found that among females with the G6PD Viangchan mutation, strenuous exercise induced a significantly higher increase in total microparticle level (an indicator of oxidative damage) compared with age-matched G6PD normal females. 69 In a study from Thailand, the authors suggested that excessive fluoride in drinking water might worsen the effect of iron deficiency anaemia, thalassemia and G6PDd. 71 In another study from Thailand, among 165 neonates, G6PDd was the main reason 22 neonates (13.4%) required exchange transfusion therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, understanding the acute exercise effect on EVs provides insight independent of cardiorespiratory fitness adaptation and weight/fat loss. However, to date there are limited studies examining the effects of acute aerobic [ 60 , 61 ] or resistance exercise [ 62 ] on EVs ( Table 1 ). For instance, Mobius-Winkler et al tested the effect of a 4 hr cycling protocol at 70% of the anaerobic threshold in 18 young, lean, healthy males [ 63 ] and found no change in endothelial EVs (CD42b − , CD42b − /CD62E + ) in the immediate postexercise period, despite increases in cytokine IL-6.…”
Section: Effects Of Acute Exercise Bouts On Extracellular Vesiclesmentioning
confidence: 99%
“…Nonetheless, these findings are consistent with Guiraud et al who showed that there was no change in endothelial EVs (CD31 + , CD62E + , and CD42b − ) or platelet EVs (CD42b + ) in 19 male coronary heart disease patients when measured up to 72 hr following either high-intensity interval or moderate-intensity cycling exercise [ 60 ]. In contrast, Chanda et al reported that a maximal bout of exercise (defined as a VO 2 max test) elicited an approximate 40% increase in platelet (CD41a) EVs in healthy adults [ 61 ]. While these later findings suggest that exercise intensity raises EV, it should be noted that maximal exercise would be considered a stressful perturbation to the system and it is known that high-intensity exercise raises oxidative stress and inflammation in the immediate postexercise period, thereby conferring a stimulus for metabolic adaptation [ 64 ].…”
Section: Effects Of Acute Exercise Bouts On Extracellular Vesiclesmentioning
confidence: 99%